Descriptive Study of Infiltration Well Design and Utilization in Sleman Regency, Special Region of Yogyakarta - Hartadi, Arhad; Supraba, Intan; Kamulyan, Budi (Universitas Negeri Yogyakarta, 2025)
In Indonesia, household-scale infiltration wells serve dual functions: managing rainwater and acting as secondary treatment systems for domestic wastewater from septic tanks. These roles require distinct designs, particularly in the arrangement and thickness of filter media. According to Indonesian technical standards (SNI – Standar Nasional Indonesia), wells designed for septic tanks use thicker, multi-layered filters that occupy most of the well's volume, while rainwater wells typically feature only a thin filter at the base. This difference reflects the higher pollutant levels in septic tank effluent compared to rainwater. Direct interviews with housing contractors in Sleman Regency, involving 836 household samples, revealed that all households repurposed rainwater infiltration well designs for managing domestic wastewater. Such practices deviate from intended design standards, raising concerns about the effectiveness of the filtration systems in these wells for contaminant removal and their potential contribution to groundwater pollution. The study further examined correlations between population density, soil characteristics, and the design and usage patterns of infiltration wells. In densely populated areas, more complex systems are often employed to manage wastewater and rainwater efficiently in limited spaces. In contrast, simpler systems are more common in less populated areas. Additionally, regions with clay-rich soils require larger wells to accommodate slower infiltration rates, while areas with sandy soils need smaller wells due to higher infiltration rates. These findings emphasize the importance of aligning infiltration well designs with both their intended purposes and local environmental conditions. Properly designed systems that manage wastewater and rainwater separately can reduce the risk of groundwater contamination, promoting more sustainable water management practices.